2018
DOI: 10.1039/c7cp07569c
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced dissolution of ibuprofen using ionic liquids as catanionic hydrotropes

Abstract: The therapeutic effectiveness of a drug largely depends on its bioavailability, and thus ultimately on its aqueous solubility. Hydrotropes are compounds able to enhance the solubility of hydrophobic substances in aqueous media and therefore are extensively used in the formulation of drugs and personal care products. Recently, some ionic liquids were shown to display a strong ability to enhance the solubility of biomolecules through hydrotropy. In this work, the impact of the ionic liquid chemical structures an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
84
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 72 publications
(85 citation statements)
references
References 57 publications
1
84
0
Order By: Relevance
“…Such result indicates that the polarity of cations plays an important role for ibuprofen dissolution. Recently, Coutinho et al found that ibuprofen showed a higher solubility in the imidazolium‐based ILs than that in the pyridinium‐, piperidinium‐, pyrrolidinium‐, tetrabutylammonium‐, and tetrabutylphosphonium‐based ILs. The obvious difference actually came from imidazolium cation with higher polarity due to a sp2 nitrogen heteroatom in the imidazolium rings that induce a dipolar character .…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Such result indicates that the polarity of cations plays an important role for ibuprofen dissolution. Recently, Coutinho et al found that ibuprofen showed a higher solubility in the imidazolium‐based ILs than that in the pyridinium‐, piperidinium‐, pyrrolidinium‐, tetrabutylammonium‐, and tetrabutylphosphonium‐based ILs. The obvious difference actually came from imidazolium cation with higher polarity due to a sp2 nitrogen heteroatom in the imidazolium rings that induce a dipolar character .…”
Section: Resultsmentioning
confidence: 99%
“…Recently, various computational methods have been used to investigate the solute‐solvent interaction at the molecular level in order to understand the major factors contributing to the favorable solvation of drugs in various ILs . For example, Paluch et al used molecular dynamics (MD) simulations to study the solvation mechanism of acetaminophen in 21 imidazolium‐based ILs.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations